A Struktur Komunitas Serangga Pengunjung pada Perkebunan Jambu Mete (Anacardium occidentale L.) Di Desa Pariti Kabupaten Kupang - Dima, Alfred O.M (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2023)
Cashew (Anacardium occidentale L.) is a flowering plant. In the flowering phase many types of insects visit the plant. This research aims to determine the types of visitors insects, community structure, and the influence of environmental factors on the level of visitor insect presence on cashew plantations in Pariti Village, Kupang Regency. This research uses a quantitative descriptive method and the determination of observation points in accomplished by purposive sampling. Observations were made in the morning at 07.00-09.00, in the afternoon at 11.00-13.00, and in the afternoon at 14.00-16.00. Sampling used sticky yellow trap and insect net. The results of the research on visitor insects consisted of 7 orders, 19 families, 29 genera, and 33 species. The diversity index (H’) obtained is 2,33 with moderate diversity criteria, the highest relative abudance index is Apis cerana (27,18%), dominace index (D) is 0,14 with moderate dominace criteria, evenness index (J) of 0,83 with low evenness criteria. The distribution criteria. The environmental parameters meter that has a significant effect on the level of visitor insect presence in temperature.